New Method for Simultaneous Arsenic and Selenium Speciation Analysis in Seafood and Onion Samples - Katarzyna Karaś; Anetta Zioła-Frankowska; Marcin Frankowski (Molecules, 2021)
This paper presents a new method for the simultaneous speciation analysis of arsenic (As(III)-arsenite, As(V)-arsenate, DMA-dimethylarsinic acid, MMA-methylarsonic acid, and AsB-arsenobetaine) and selenium (Se(IV)-selenite, Se(VI)-selenate, Se-Methionine, and Se-Cystine), which was applied to a variety of seafood and onion samples. The determination of the forms of arsenic and selenium was undertaken using the High-Performance Liquid Chromatography Inductively Coupled Plasma Mass Spectrometry (HPLC–ICP–MS) analytical technique. The separation of both organic and inorganic forms of arsenic and selenium was performed using two analytical columns: an anion exchange column, Dionex IonPac AS22, containing an alkanol quaternary ammonium ion, and a double bed cation–anion exchange guard column, Dionex Ion Pac CG5A, containing, as a first layer, fully sulfonated latex for cation exchange and a fully aminated layer for anion exchange as the second layer. The ammonium nitrate, at pH = 9.0, was used as a mobile phase. The method presented here allowed us to separate the As and Se species within 10 min with a suitable resolution. The applicability was presented with different sample matrix types: seafood and onion.